Curriculum Literacy And Writing Activities Specific to Gifted Students: Teachers’ Experiences - İhtiyar Şahin, Seda (Research Trends In Educational Sciences, 2025)
This study examines the competencies and practices of teachers in the context of curriculum literacy and activity design for gifted students. Gifted individuals, with their rapid learning capacities, advanced cognitive skills, and creative potential, require individualized and innovative approaches beyond standard educational programs. In Turkey, the education of these students is primarily provided through Science and Art Centers (BİLSEM). The research employs a mixed-methods approach to evaluate the curriculum literacy levels and activity design processes of BİLSEM teachers.Quantitative data were collected from 203 teachers, while qualitative data were obtained through interviews with 20 teachers. The results of the quantitative analysis revealed that teachers' curriculum literacy levels were "very high," although deficiencies were identified in areas such as writing evaluation criteria. Qualitative findings indicated that teachers designed student-centered activities that considered individual differences and integrated technology. Additionally, project-based learning, creative thinking, and real-life problem-solving approaches were found to be commonly used in these activities.The findings suggest that teachers possess strong competencies in content organization and activity design, but there is a need for further professional development in evaluation processes. This study provides significant insights for the development of educational programs aimed at maximizing the potential of gifted students.